Evaluation of endoscopic retrograde cholangiopancreatography using a newly developed short‐type single‐balloon endoscope in patients with altered gastrointestinal anatomy. (April 2014) - Shimatani, Masaaki; Takaoka, Makoto; Ikeura, Tsukasa; Mitsuyama, Toshiyuki; Okazaki, Kazuichi
Abstract : Background and Aim: Endoscopic approaches for pancreatobiliary diseases in patients with altered gastrointestinal anatomy had been impractical until the development of balloon‐assisted endoscope (BAE) made it feasible. The aim of the present study was to evaluate the usefulness of a newly developed short‐type single‐balloon endoscope (s‐SBE) for endoscopic retrograde cholangiopancreatography (ERCP) in patients with altered gastrointestinal anatomy. Methods: From March 2013 to November 2013, s‐SBE‐assisted ERCP was done in our hospital in 26 postoperative patients who had surgically altered anatomy. We retrospectively evaluated the success rate of reaching the blind end, the mean time required to reach the blind end, the diagnostic success rate, the therapeutic success rate, the mean procedure time, and complications. Results: The success rate of reaching the blind end was 92.3%. The mean time required to reach the blind end was 25.3 min. The diagnostic success rate was 91.7%. The diagnostic success rate for naïve papilla was 75%. The mean procedure time was 56.0 min. The success rate of overall s‐SBE‐assisted ERCP was 84.6%. The complication rate was 3.8%. Conclusion: Diagnostic and therapeutic ERCP using a newly developed s‐SBE is sufficiently effective.